2017
DOI: 10.18517/ijaseit.7.2.1678
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting The Success of Incubators and The Moderating Role of Information and Communication Technologies

Abstract: Business incubators can help young firms to survive during their first years. They are considered to be an entrepreneurial and economic development instrument that can increase the creativity of new firms including small and mid-sized enterprises and that can support them in the early stage of development which is the most vulnerable stage of their existence. Small and mid-sized enterprises are crucial for enhancing innovation, productivity, competitiveness, social cohesion, and economic development in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Moreover, customer relationship management (CRM) in the Middle East has become a key strategy for a small company, indicate the need for more SMEs to implement for effective business operations. It is evident that CRM also develops a high-performance strategy and facilitate value-added, technical, and innovative mechanisms to achieve the ultimate aim of obtaining a competitive edge over competitors [ 1 , 41 ].…”
Section: Customer Relationship Management (Crm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, customer relationship management (CRM) in the Middle East has become a key strategy for a small company, indicate the need for more SMEs to implement for effective business operations. It is evident that CRM also develops a high-performance strategy and facilitate value-added, technical, and innovative mechanisms to achieve the ultimate aim of obtaining a competitive edge over competitors [ 1 , 41 ].…”
Section: Customer Relationship Management (Crm)mentioning
confidence: 99%
“…The term ICT is a combination of two terms: information technology (IT) and communications. Information technology refers to any computing technology, such as networks, hardware, software, communication devices, communication infrastructure [ 1 ], systems and solutions, and the internet IT can lower production and labor costs, add value to products and services, and increase a company’s competitive advantage. Some studies and reports have shown that IT is a means that could enhance the business process [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the farmer is risk-averse, it will encourage the farmer to become an entrepreneur (Hsieh, Parker, & van Praag, 2017). Entrepreneurial behavior is essential in the field of farming and agribusiness (Ume et al, 2020), agro-tourism (Yuan, Liu, Ju, & Li, 2017), and SME activities (Alzaghal & Mukhtar, 2017;Auwal, Mohamed, Shamsudin, Sharifuddin, & Ali, 2020) and it is reflected by a proactive attitude, results-oriented, and commitment to facing competitors. Based on the analysis results, the task and outcome-oriented variables (X2.2 = 0.829) play the most dominant role in constructing farmer's entrepreneurship.…”
Section: Effect Of Farmer's Entrepreneurship On the Rice Farming Perf...mentioning
confidence: 99%
“…Critical Success Factors are defined as the major measure of a company's operations essential to its success (Alzaghal and Mukhtar, 2017). In this study, three factors are considered, (1) Technology, (2) Organization, (3) Individual.…”
Section: Current Study Of Critical Success Factorsmentioning
confidence: 99%